Sol-Gel-Hydrothermal Synthesis of the Heterostructured TiO2/N-Bi2WO6 Composite with High-Visible-Light- and Ultraviolet-Light-Induced Photocatalytic Performances - Jiang Zhang; Zheng-Hong Huang; Yong Xu; Feiyu Kang (International Journal of Photoenergy)
The heterostructured TiO2/N-Bi2WO6 composites were prepared by a facile sol-gel-hydrothermal method. The phase structures, morphologies, and optical properties of the samples were characterized by using X-ray powder diffraction (XRD), scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM), energy dispersive spectroscopy (EDS), and UV-vis diffuse reflectance spectroscopy. The photocatalytic activities for rhodamine B of the as-prepared products were measured under visible and ultraviolet light irradiation at room temperature. The TiO2/N-Bi2WO6 composites exhibited much higher photocatalytic performances than TiO2 as well as Bi2WO6. The enhancement in the visible light photocatalytic performance of the TiO2/N-Bi2WO6 composites could be attributed to the effective electron-hole separations at the interfaces of the two semiconductors, which facilitate the transfer of the photoinduced carriers.